Increased alpha and beta cell mass during mouse pregnancy is not dependent on transdifferentiation. Issue 5 (March 2021) - Szlapinski, Sandra K; Bennett, Jamie; Strutt, Brenda J; Hill, David J
Maternal pancreatic beta-cell mass (BCM) increases during pregnancy to compensate for relative insulin resistance. If BCM expansion is suboptimal, gestational diabetes mellitus can develop. Alpha-cell mass (ACM) also changes during pregnancy, but there is a lack of information about α-cell plasticity in pregnancy and whether α- to β-cell transdifferentiation can occur. To investigate this, we used a mouse model of gestational glucose intolerance induced by feeding low-protein (LP) diet from conception until weaning and compared pregnant female offspring to control diet-fed animals. Control and LP pancreata were collected for immunohistochemical analysis and serum glucagon levels were measured. In order to lineage trace α- to β-cell conversion, we utilized transgenic mice expressing yellow fluorescent protein behind the proglucagon gene promoter (Gcg-Cre/YFP) and collected pancreata for histology at various gestational timepoints. Alpha-cell proliferation increased significantly at gestational day (GD) 9.5 in control pregnancies resulting in an increased ACM at GD18.5, and this was significantly reduced in LP animals. Despite these changes, serum glucagon was higher in LP mice at GD18.5. Pregnant Gcg-Cre/YFP mice showed no increase in the abundance of insulin + YFP + glucagon – cells (phenotypic β-cells). A second population of insulin + YFP + glucagon + cells was identified which also did not alter during pregnancy. However, there was an altered anatomical distribution within islets with fewer insulin + YFP + glucagon – cells but more insulin + YFP + glucagon + cells being present in the islet mantle at GD18.5. These findings demonstrate that dynamic changes in ACM occur during normal pregnancy and were altered in glucose-intolerant pregnancies.